Tuning crystalline ordering by annealing and additives to study its effect on exciton diffusion in a polyalkylthiophene copolymer. Issue 19 (4th May 2017) - Chowdhury, Mithun; Sajjad, Muhammad T.; Savikhin, Victoria; Hergué, Noémie; Sutija, Karina B.; Oosterhout, Stefan D.; Toney, Michael F.; Dubois, Philippe; Ruseckas, Arvydas; Samuel, Ifor D. W.
Abstract : The influence of processing conditions on singlet exciton diffusion is studied in films of a conjugated copolymer P3HT- co -P3DDT. Abstract : The influence of various processing conditions on the singlet exciton diffusion is explored in films of a conjugated random copolymer poly-(3-hexylthiophene- co -3-dodecylthiophene) (P3HT- co -P3DDT) and correlated with the degree of crystallinity probed by grazing incidence X-ray scattering and with exciton bandwidth determined from absorption spectra. The exciton diffusion coefficient is deduced from exciton–exciton annihilation measurements and is found to increase by more than a factor of three when thin films are annealed using CS2 solvent vapour. A doubling of exciton diffusion coefficient is observed upon melt annealing at 200 °C and the corresponding films show about 50% enhancement in the degree of crystallinity. In contrast, films fabricated from polymer solutions containing a small amount of either solvent additive or nucleating agent show a decrease in exciton diffusion coefficient possibly due to formation of traps for excitons. Our results suggest that the enhancement of exciton diffusivity occurs because of increased crystallinity of alkyl-stacking and longer conjugation of aggregated chains which reduces the exciton bandwidth.